CAMBIOS EN LA GEOPOLÍTICA Y OCUPACIÓN DEL TERRITORIO: PERÚ 2000-2020 - JURADO NÁJERA, Joel (2023)
With the Washington Consensus since 1990, the predominance of investments by transnational companies in the private exploitation of extractive mining resources was given way. American and European companies acquired most of the mining and energy deposits that were in the hands of the Peruvian State. These continued to operate under the enclave-type territorial occupation pattern, without major linkages with the regional economy or its rural environment. Since the beginning of this century, Chinese investment began to acquire the mining companies with the greatest technological development and future potential, at the same time weaving the so-called Silk Road, on the basis of transversal economic corridors, diversifying their investments in different lines of activity, projecting and modernizing the multivariate infrastructure in the north, center and south macro-regions leading to global ports that will operate in a network on the Peruvian coast of the Pacific Ocean, highlighting the railways and waterways for the bioceanic integration with Brazil and Bolivia and the Atlantic.